2011
DOI: 10.5539/ijbm.v6n9p141
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Counselors’ Self-Efficacy: Implication for Career Counseling

Abstract: The present study was intended to measure Malaysian counselors' self-efficacy. The finding shows that Malaysian school counselors have high self-efficacy. Self-efficacy correlated significantly with work experience as a counselor. The study also shows that counselors with postgraduate education are more effacious than their counterparts who have an undergraduate degree only. Counselors' self-efficacy does not differ as a function of gender and program of study. However, what is important is their experiences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
1
0
5
Order By: Relevance
“…This results imply that higher education students in Nigeria who are high in any of the predictor variables (career self-efficacy sources, personal goal orientation, career future concern, and perceived social support) are more likely to be high in career adaptability skill. On self-efficacy for example, the results of this study is in consonance with reports from other studies which found that career self-efficacy or self-efficacy sources significantly predicted career adaptability skill among youth, students of higher education, as well as existing workers Gadassi et al, 2013a;2013b;Nota et al, 2007;Bakar, 2011;Loo and Choy, 2013). The results of this study is also consistent with some previous studies conducted among university students which reported that career concerns, learning and performance-prove goal orientations predicted career adaptability skill (Creed and Fallon, 2009;Yousefi et al, 2013).…”
Section: Findings and Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…This results imply that higher education students in Nigeria who are high in any of the predictor variables (career self-efficacy sources, personal goal orientation, career future concern, and perceived social support) are more likely to be high in career adaptability skill. On self-efficacy for example, the results of this study is in consonance with reports from other studies which found that career self-efficacy or self-efficacy sources significantly predicted career adaptability skill among youth, students of higher education, as well as existing workers Gadassi et al, 2013a;2013b;Nota et al, 2007;Bakar, 2011;Loo and Choy, 2013). The results of this study is also consistent with some previous studies conducted among university students which reported that career concerns, learning and performance-prove goal orientations predicted career adaptability skill (Creed and Fallon, 2009;Yousefi et al, 2013).…”
Section: Findings and Implicationssupporting
confidence: 91%
“…Career decision-making self-efficacy was significantly related to learning goal orientation through the mediation of high student rating of parental support (Garcia et al, 2012). Self-efficacy also correlated significantly with work experience of counselors in Malaysia, and no differences were found in gender or program of study (Bakar, 2011). Career self-efficacy beliefs correlated with career exploration, and career self-efficacy beliefs also predicted career exploration .…”
Section: Career Self-efficacy Sourcesmentioning
confidence: 90%
“…(Eysenck, 1992) á©HQC 'G ÖfGƒ÷G √ò¡d k ɪ¡e k Éë«°VƒJ OÉ©HC 'G √òg ∫ÓN øe (Eysenck, 1992 (Eysenck, 1992) . (Bandura, 1994, 195) ¿ƒ°SQGódG 46 ,45 ,40 ,35 ,30 ,23 ,20 ,18 ,14 ,9 ,3 ,2 •É°ùÑf'G á«HÉéjE 'G 47 ,43 ,39 ,33 ,29 ,28 ,25 ,22 ,19 ,5 ,1 á«Ñ∏°ùdG 13 ÜòµμdG á«HÉéjE 'G 41 ,36 ,12 ,8 á«Ñ∏°ùdG 32 ,31 ,27 ,24 ,17 ,15 ,10 ,4 á«fÉgòdG á«Ñ∏°ùdG 48 , 44 ,42 ,38 ,37 ,34 ,26 ,21 ,16 ,11 ,7 47 ,40 ,38 ,37 ,27 ,24 ,23 ,18 ,12 ,11 ,10 (Philip, 1992) (Schmidt & Strong, 1990) ¬«dE G π°UƒJ Ée ™e áé«àf ÚH ¥ÉØJ'G ΩóY ™Lôj óbh (Philip, 1992) (Schmidt & Strong,1990) (Johanna & Changming, 2007) á°SGQOh äGÒ¨àà á°UÉÿGh (Bakar et al, 2011) á°SGQóc iôNC G äÉ°SGQO èFÉàf ¢ †©H ™e ∞∏àîJh…”
Section: áEó≤ÿgunclassified
“…Κατόπιν, περιγράφεται το θεωρητικό και ερευνητικό πλαίσιο που έχει διαμορφωθεί έως σήμερα όσον αφορά στις σχέσεις της αυτοαποτελεσματικότητας για την άσκηση συμβουλευτικής με άλλους σημαντικούς παράγοντες στο συμβουλευτικό έργο, δημογραφικά στοιχεία και χαρακτηριστικά προσωπικότητας του συμβούλου. Έμφαση δίνεται στη σχέση της αυτοαποτελεσματικότητας με τη συμβουλευτική πράξη και την αποτελεσματικότητα του συμβούλου (Bakar, Zakaria, & Mohamed, 2011. Larson et al, 1999.…”
Section: σκοπός της μελέτηςunclassified
“…Φυσικά, το συγκεκριμένο αποτέλεσμα ενδέχεται να αναδεικνύει την ανάγκη για παροχή περισσότερων εμπειριών πρακτικής άσκησης στους φοιτητές του συγκεκριμένου πανεπιστημίου (Kiralp, 2015). Bakar et al, 2011. Harris, 2007.…”
Section: αυτοαποτελεσματικότητα για την άσκηση συμβουλευτικής επίδοση του συμβούλου και αποτελέσματα για τους πελάτεςunclassified